A parasitic nematode releases cytokinin that controls cell division and orchestrates feeding site formation in host plants - Siddique, Shahid; Radakovic, Zoran S; De La Torre, Carola M; Chronis, Demosthenis; Novák, Ondřej; Ramireddy, Eswarayya; Holbein, Julia; Matera, Christiane; Hütten, Marion; Gutbrod, Philipp; Anjam, Muhammad Shahzad; Rozanska, Elzbieta; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2015)
Sedentary plant-parasitic cyst nematodes are biotrophs that cause significant losses in agriculture. Parasitism is based on modifications of host root cells that lead to the formation of a hypermetabolic feeding site (a syncytium) from which nematodes withdraw nutrients. The host cell cycle is activated in an initial cell selected by the nematode for feeding, followed by activation of neighboring cells and subsequent expansion of feeding site through fusion of hundreds of cells. It is generally assumed that nematodes manipulate production and signaling of the plant hormone cytokinin to activate cell division. In fact, nematodes have been shown to produce cytokinin in vitro; however, whether the hormone is secreted into host plants and plays a role in parasitism remained unknown. Here, we analyzed the spatiotemporal activation of cytokinin signaling during interaction between the cyst nematode, Heterodera schachtii, and Arabidopsis using cytokinin-responsive promoter:reporter lines. Our results showed that cytokinin signaling is activated not only in the syncytium but also in neighboring cells to be incorporated into syncytium. An analysis of nematode infection on mutants that are deficient in cytokinin or cytokinin signaling revealed a significant decrease in susceptibility of these plants to nematodes. Further, we identified a cytokinin-synthesizing isopentenyltransferase gene in H. schachtii and show that silencing of this gene in nematodes leads to a significant decrease in virulence due to a reduced expansion of feeding sites. Our findings demonstrate the ability of a plant-parasitic nematode to synthesize a functional plant hormone to manipulate the host system and establish a long-term parasitic interaction.
Keywords: cytokininy; Host-Parasite Interactions; zvířata; nemoci rostlin; signální transdukce; Base Sequence; Nematoda; interakce hostitele a parazita; Plant Diseases; sekvence nukleotidů; hlístice; Arabidopsis; Animals; Cytokinins; Molecular Sequence Data; molekulární sekvence - údaje; Signal Transduction